The Physicochemical Characterization, Gelatinization Profile, and Proximate Analysis of Sweet Potato Starch (Ipomoea batatas L.) White, Yellow, and Purple - Triana Kusumaningsih; Maulidan Firdaus; Fyan Tri Istiqomah Juneasri (Universitas Jenderal Soedirman, 2022)
Sweet potato (Ipomoea batatas L.) has a considerable potency to be developed in Indonesia because of its high nutritional content and spacious application of sweet potato starch in food and non-food fields. Physicochemical characterization, gelatinization profile, and proximate analysis of sweet potato starch white, yellow, and purple has been carried out. Initially, extraction of starch from white, yellow, and purple sweet potato flour was done using a maceration technique. The starch extract was then analysed to determine its physicochemical properties such as pH, density, boiling point, melting point, swelling capacity, and solubility in water, as well as morphological surface using Scanning Electron Microscopy (SEM). The gelatinization profile of sweet potato starch was measured using the Rapid Visco Analyzer (RVA). The proximate composition of sweet potato starch was also determined. The results showed that yellow sweet potato starch has a high amylose content of 28.17% which thus leads to difficulty in absorbing water, increasing the gelatinization temperature and affecting the structural stability of the starch. The molecular structure of amylose and amylopectin is the main factor influencing the determination of the physicochemical characterization of sweet potato starch. Proximate analysis of sweet potato starch showed high content of amylose (28.17%), water (17.03%), and protein (5.21%) with low amylopectin (71.83%), minerals (1.09%), fat (0.09%), and carbohydrates (76.9%) content. The three varieties of sweet potato show extraordinary potential in food industrial applications because they play a huge part in deciding the suitability of sweet potato starch for specific requirements and interest in developing new and remarkable starch sources.